Third order nonlinearity and optical power limiting studies of PS/ZnO nanocomposite foils for photonic applications. (1st October 2022) - Barala, Monika; Maidur, Shivaraj R; Mohan, Devendra; Sanghi, Sujata
Abstract: The present work focuses on the preparation of Polystyrene (PS) and PS/ZnO nanocomposite foils by solution casting method and study their structural and nonlinear optical (NLO) characterizations. The Zinc Oxide (ZnO) nanoparticles were synthesized by Sol-gel method. Structural analysis of the prepared nanocomposite foils was carried out by x-ray diffraction (XRD) with an estimated average crystallite size of 27.33 nm. UV–vis-NIR spectra reveal that the nanocomposite foils are transparent in the visible region. FESEM micrographs show the surface morphology of the prepared nanocomposite foils. Energy Dispersive x-ray Spectroscopy (EDX) of the prepared foils confirmed the compositional and spatial distribution of the elements. The NLO properties such as nonlinear absorption coefficient ( β ), nonlinear index of refraction (n2 ), and third-order nonlinear susceptibility χ 3 were investigated by Z-scan technique at a wavelength of 532 nm and 200 mW with field intensity I 0 = 5.43 KW cm − 2 . The values of β were found to bein the order of ∼ 10 −7 cm W −1, n2 in the order of ∼10 −12 cm 2 W −1 and χ 3 in the range 4.99 × 10 −7 – 38.7 × 10 −7 e.s.u. Further, the optical power limiting threshold was calculated to be 3.646 KW cm −2 for 8 wt % of PS/ZnO nanocomposite foil which is a better candidate to act as an optical limiter. The figure of merit has also been determined that establishes the suitability of nanocomposite foils for optical limiting and/or optical switching applications in the visible region.